Recurrence and functional results after open versus conventional laparoscopic versus robot-assisted laparoscopic rectopexy for rectal prolapse: a case–control study - de Hoog, Dominique E. N. M. (Springer-Verlag, 2009)
PURPOSE: This study was designed to evaluate recurrence and functional outcome of three surgical techniques for rectopexy: open (OR), laparoscopic (LR), and robot-assisted (RR). A case–control study was performed to study recurrence after the three operative techniques used for rectal procidentia. The secondary aim of this study was to examine the differences in functional results between the three techniques. MATERIALS AND METHODS: All consecutive patients who underwent a rectopexy between January 2000 and September 2006 enrolled in this study. Peri-operative data were collected from patient records and functional outcome was assessed by telephonic questionnaire. RESULTS: Eighty-two patients (71 females, mean age 56.4 years) underwent a rectopexy for rectal procidentia. Nine patients (11%) had a recurrence; one (2%) after OR, four (27%) after LR, and four (20%) after RR. RR showed significantly higher recurrence rates when controlled for age and follow-up time compared to OR, (p = 0.027), while LR showed near-significant higher rates (p = 0.059). Functional results improved in all three operation types, without a difference between them. CONCLUSIONS: LR and RR are adequate procedures but have a higher risk of recurrence. A RCT is needed assessing the definitive role of (robotic assistance in) laparoscopic surgery in rectopexy.